RETRACTED: Estimation the state of power quality in distribution networks using fuzzy logic - Kholiddinov Ilkhombek; Eraliyev Abdunabi; Sharobiddinov Mirzokhid; Tukhtashev Alisher; Qodirov Afzal; Khaqiqov Anvar (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001